2009
DOI: 10.1080/00016340802595993
|View full text |Cite
|
Sign up to set email alerts
|

Early signs of maternal iron deficiency do not influence the iron status of the newborn, but are associated with higher infant birthweight

Abstract: In a well-nourished maternal population, lower maternal iron status did not affect the iron accumulation on the fetal side. However, longer duration of pregnancy and growth of the fetus appeared to be associated with a lower amount of iron for Hb synthesis in maternal red blood cells, as reflected by the increased maternal %HYPOm, birthweight and length of gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 57 publications
(66 reference statements)
3
16
0
1
Order By: Relevance
“…At the earliest assessment at one and two months, the iron endowment showed enormous variation. This wide range in the size of the iron endowment has been previously shown by us [4,5,6] and others [7,8,9,10,11,12,13,14,15,16,17,18]. Only a small proportion of that variation was explained by iron status of the mother whereas its bulk remained unexplained.…”
Section: Discussionsupporting
confidence: 74%
“…At the earliest assessment at one and two months, the iron endowment showed enormous variation. This wide range in the size of the iron endowment has been previously shown by us [4,5,6] and others [7,8,9,10,11,12,13,14,15,16,17,18]. Only a small proportion of that variation was explained by iron status of the mother whereas its bulk remained unexplained.…”
Section: Discussionsupporting
confidence: 74%
“…In similar studies, maternal ferritin levels were shown to be in accordance with chord blood ferritin levels of the babies (21,22). However, studies have shown that inadequate iron status during pregnancy does not cause inhibition of transfer of iron to the baby, if the mother's nutrition is adequate (23). In another study which is similar to our study, no significant difference was found in babies in terms of iron levels at the time of delivery, although half of the pregnant women had iron deficiency and anemia (24).…”
Section: Discussionsupporting
confidence: 73%
“…There are opposite data from developing countries where, among well-nourished maternal population, lower iron status of expecting mothers was associated with a higher birth weight and a longer duration of pregnancy (26). The results of our research show that the anemic mothers’ newborns weighted in average 3048,00 g and were 553,00 g easier compared to the newborns of the control group.…”
Section: Discussionmentioning
confidence: 94%